Study on Benign Episodic Unilateral - Ozkara, B.; Budak, F. (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Benign unilateral episodic mydriasis is a similar condition in which young individuals, mainly women, experience intermittent periods of pupillary asymmetry mydriasis. Each incident is self-contained, and no systemic or neurologic disease has been linked to the circumstance. Usually related to migraine, some authors classify it as a limited form of ophthalmoplegic migraine, although our patient have been described with no accompanying headache. She complained of anxiety, irritability and insomnia. Selective serotonin reuptake inhibitors (SSRIs) are helpful in the treatment of depression and generalised anxiety disorder, and are frequently recommended as the pharmacotheraphy of choice.The central inhibitory effects of SSRI are thought to extend to dilation linked neurons that inhibit the E.W. nucleus, therefore SSRI would suppress BUEM as well. The cause of the underlying physiopathology is unclear, however it could be parasympathetic insufficiency or sympathetic hyperactivity affecting the iris. The study objectives is the probable pathophysology of BUEM that intermittent inhibition of dilation-corelated neurons in the Edinger Westpal nucleus are responsible for the pupillary dilatations seen in BUEM.